2015
DOI: 10.3389/frobt.2015.00025
|View full text |Cite
|
Sign up to set email alerts
|

Encoded and Crossmodal Thermal Stimulation through a Fingertip-Sized Haptic Display

Abstract: Haptic displays aim at artificially creating tactile sensations by applying tactile features to the user's skin. Although thermal perception is a haptic modality, it has received scant attention possibly because humans process thermal properties of objects slower than other tactile properties. Yet, thermal feedback is important for material discrimination and has been used to convey thermally encoded information in environments in which vibrotactile feedback might be masked by noise and/or movements. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…If there is thermo-haptic feedback, more realistic touch can be delivered to users when manipulating hot water cups or objects in AR and VR mimicking daily life. In addition, the temperature is used as a way to improve object identification in virtual and remote operating environments, and it is also an important sense when inferring properties [23][24][25][26][27]. Therefore, one can convey a realistic sense to the user in a virtual environment by reproducing thermal sensations in a haptic device [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…If there is thermo-haptic feedback, more realistic touch can be delivered to users when manipulating hot water cups or objects in AR and VR mimicking daily life. In addition, the temperature is used as a way to improve object identification in virtual and remote operating environments, and it is also an important sense when inferring properties [23][24][25][26][27]. Therefore, one can convey a realistic sense to the user in a virtual environment by reproducing thermal sensations in a haptic device [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…These vibration amplitudes are clearly perceptible. For this wire because the resistance was 69 V and the power supply voltage was 24 V, the power consumption was 24 2 /69 Â 0.2 ¼ 1.67 W. In a practical situation, we must consider how many pins are simultaneously driven and how frequently the tactile display needs to be updated, but we believe the overall power consumption can be kept lower than 10 W.…”
Section: C) Discussionmentioning
confidence: 99%
“…The adopted design solutions were implemented and evaluated in the prototype of a highly wearable fingertip device. Final experimental results show how the implementation of the proposed method is capable of an effective haptic It proposes development of different devices capable of specific cutaneous feedback and cues, such as contact-no contact condition, modulation of grasping forces [19], contact orientation [3], area of contact [5], stretch and indentation [12], thermal [8], multimodal feedback [6,21]. A comprehensive review of wearable haptic devices including a taxonomy can be found in [17].…”
Section: Introductionmentioning
confidence: 99%